The Application of Neural Networks in Stock-Exchange Investing - Ogrodnik, Radoslaw; Buus, Tomáš, 1977-; Poborský, František; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2015)
The experiment performed showed that predicting stock movements accurately with a neural networks is a very challenging task. Even obtaining low error in the training process, does not indicate that one will receive high quality predictions in the future. Similarly potential gain obtained be the network in the analysed period does not have to repeat in the next one. The reason behind, is that situations which occurred in the past, do not have to repeat. Moreover there are numerous factors that may influence index's future behaviour which simply cannot be even taken into account by an artificial model. However, even if it is difficult to create a network which would provide an output accurate enough to be used as an only indicator, neural networks are still an interesting tool and may perform well as a guidance for an investor.
Vedoucí práce: Tomáš Buus
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2015
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2015
Způsob přístupu: Internet
Keywords: diplomové práce; master's theses; finance and accounting for common europe [obor dipl. práce]